A Community of Practice for Knowledge Translation Trainees: An Innovative Approach for Learning and Collaboration1. Issue 4 (September 2013) - Urquhart, Robin; Cornelissen, Evelyn; Lal, Shalini; Colquhoun, Heather; Klein, Gail; Richmond, Sarah; Witteman, Holly O.
Abstract A growing number of researchers and trainees identify knowledge translation (KT) as their field of study or practice. Yet, KT educational and professional development opportunities and established KT networks remain relatively uncommon, making it challenging for trainees to develop the necessary skills, networks, and collaborations to optimally work in this area. The Knowledge Translation Trainee Collaborative is a trainee‐initiated and trainee‐led community of practice established by junior knowledge translation researchers and practitioners to: examine the diversity of knowledge translation research and practice, build networks with other knowledge translation trainees, and advance the field through knowledge generation activities. In this article, we describe how the collaborative serves as an innovative community of practice for continuing education and professional development in knowledge translation and present a logic model that provides a framework for designing an evaluation of its impact as a community of practice. The expectation is that formal and informal networking will lead to knowledge sharing and knowledge generation opportunities that improve individual members' competencies (eg, combination of skills, abilities, and knowledge) in knowledge translation research and practice and contribute to the development and advancement of the knowledge translation field.